The impact of risk attitudes on entrepreneurial survival - Marco Caliendo; Frank M. Fossen; Alexander S. Kritikos (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
Risk attitudes have an impact on not only the decision to become an entrepreneur but also the survival and failure rates of entrepreneurs. Whereas recent research underpins the theoretical proposition of a positive correlation between risk attitudes and the decision to become an entrepreneur, the effects on survival are not as straightforward. Psychological research posits an inverse U-shaped relationship between risk attitudes and entrepreneurial survival. On the basis of recent waves of the German Socio-Economic Panel (SOEP), we examine the extent to which risk attitudes influence survival rates of entrepreneurs. The empirical results confirm that persons whose risk attitudes are in the medium range survive significantly longer as entrepreneurs than do persons with particularly low or high risks.
Keywords: D81; J23; M13; 330; Entrepreneurship; Risk Attitudes; Survival and Failure; Unternehmer; Risikopräferenz; Unternehmensgründung; Unternehmensentwicklung; Deutschland